A phylogenetic study of Crepis L. species sect. Barkhausia (Asteraceae) using low-copy nuclear genes (gsh1, sqs) and plastid genes (rps16, matK1) - Esklual, Ghalia A. Y.; Justus Liebig University Giessen (My University, 2017)
The genus Crepis L. belongs to the family Asteraceae Martinov, tribe Cichorieae Lam. & DC. Babcock (1947b) divided the genus into 27 sectional ranks. A revised infrageneric classification based on molecular tools (Enke & Gemeinholzer 2008, Enke 2009) maintained 21 of Babcock s 27 sections but revised the circumscription of some of them. Section Barkhausia Moench with 12~14 species revealed to be monophyletic, however, incongruences between nuclear and plastid markers were recorded. The actual analysis was conducted to remove this ambiguity, detangle the evolutionary relationships of Crepis section Barkhausia, and to find out if these relationships are the result of reticulate evolution via hybridization across lineages or of incomplete lineage sorting. In most Angiosperms, the chloroplasts are maternally inherited, while the nuclear genome can be indicative of hybridization events. To reconstruct the phylogeny within section Barkhausia, the low-copy nuclear markers gamma-glutamylcysteine synthetase (gsh1) and squalene synthase (sqs) and the chloroplast markers ribosomal protein S16 (rps16) and maturase K (matK1) were analysed, also in combination with the multicopy nuclear internal transcribed spacer (ITS) of the previous studies mentioned above. 12 Crepis species which belong to section Barkhausia were analysed, and Hispidella hispanica L. was used as an outgroup. Maximum Parsimony and Maximum Likelihood algorithms and reticulation and network analyses were used to analyse different datasets (all markers, concatenated, and reduced).The analysis revealed the low-copy nuclear markers gsh1 and sqs to be of multi-copy origin. The different multiple copies within individuals were indicative of different evolutionary scenarios, which complicated the phylogenetic reconstruction and resulted in weak or non-resolved phylogenetic relationships. Four and five different copy types among species were identified in sqs and gsh1, respectively, and recombination analyses confirmed locus activities without recombination among the different copies. Careful analysis by hand resulted in copy sorting among individuals for phylogenetic analysis.The comparison between the maternally inherited chloroplast markers and the nuclear markers, which are indicative for hybridization, showed topological disagreements, which confirms the earlier findings of Enke & Gemeinholzer (2008). The patterns are indicative of reticulate evolution, which can be due to incongruences resulting from gene duplication or incomplete lineage sorting (like C. foetida spp. commutata and C. alpina; C. kotschyana and C. triasii), and / or to hybridization (like C. rubra and C. tybakiensis; C. pusilla and C. zacintha). These patterns point to very recent speciation events in the Crepis species analysed in the current study. In combined nuclear and plastid tree analyses, C. triasii clustered paraphyletic to the outgroup taxon Hispidella hispanica and rendered Crepis species section Barkhausia in its current circumscription polyphyletic.

Die Gattung Crepis L. gehört zur Familie der Asteraceae Martinov, Tribus Cichorieae Lam. & DC. Babcock (1947b) unterteilte die Gattung in 27 Sektionen. Eine revidierte infragenerische Klassifikation, die auf molekularen Werkzeugen basiert (Enke & Gemeinholzer 2008, Enke 2009), behielt 27 der 21 Sektionen von Babcock bei, veränderte aber die Abgrenzungen einiger Sektionen. Die Sektion Barkhausia Moench mit 12 - 14 Arten erwies sich als monophyletisch, allerdings wurden Inkongruenzen zwischen nukleären Markern und Plastidenmarkern festgestellt. Die vorliegende Analyse diente dazu, diese Unklarheiten zu beseitigen, die evolutionären Beziehungen der Crepis-Sektion Barkhausia zu entwirren und herauszufinden, ob diese Beziehungen das Ergebnis von retikulärer Evolution durch linienübergreifende Hybridisierung oder von unvollständigem lineage Sorting sind. Bei den meisten Angiospermen werden die Chloroplasten maternal vererbt, während das nukleäre Genom Hybridisierungsvorgänge anzeigen kann. Um die Phylogenie innerhalb der Sektion Barkhausia zu rekonstruieren, wurden die nukleären low-copy-Marker Gamma-Glutamylcystein-Synthetase (gsh1) und Squalen-Synthase (sqs) sowie die Chloroplastenmarker ribosomales Protein S16 (rps16) and Maturase K (matk1) analysiert, auch in Kombination mit dem nukleären multi-copy internal transcribed spacer (ITS) aus den o. g. vorhergehenden Studien. 12 zur Sektion Barkhausia gehörende Crepis-Arten wurden analysiert, und Hispidella hispanica L. wurde als Außengruppe verwendet. Maximum-Parsimony- und Maximum-Likelihood-Algorithmen sowie Retikulations- und Netzwerkanalysen wurden durchgeführt, um verschiedene Datensätze zu analysieren (alle Marker, verknüpft und reduziert).Die Analyse deckte auf, dass die nukleären low-copy-Marker gsh1 and sqs einen multi-copy-Ursprung haben. Die verschiedenen multiplen Kopien innerhalb der Individuen deuteten auf verschiedene evolutionäre Szenarien hin, was die phylogenetische Rekonstruktion verkomplizierte und zu schwachen oder ungeklärten phylogenetischen Beziehungen führte. Vier bzw.fünf verschiedene Kopie-Typen zwischen den Arten wurden für gsh1 bzw. sqs identifiziert, und Rekombinationsanalysen bestätigten Lokusaktivitäten ohne Rekombination zwischen den verschiedenen Kopien. Durch sorgföltige Analysen per Hand wurden die Kopien für die phylogenetische Analyse auf die Individuen verteilt.Der Vergleich zwischen den maternal vererbten Chloroplastenmarkern und den Hybridisierung anzeigenden nukleären Markern zeigte topologische Unstimmigkeiten, was die früheren Ergebnisse von Enke & Gemeinholzer (2008) bestätigt. Die Muster deuten auf retikuläre Evolution hin, die beruhen kann auf Inkongruenzen aufgrund von Genduplikation oder unvollständigem lineage Sorting (wie C. foetida spp. commutata und C. alpina; C. kotschyana und C. triasii), und / oder auf Hybridisierung (wie C. rubra und C. tybakiensis; C. pusilla und C. zacintha). Diese Muster weisen auf sehr kürzlich erfolgte Speziationsprozesse in den in der vorliegenden Studie untersuchten Crepis-Arten hin. In den kombinierten Analysen von nukleärem Baum und Plastidenbaum gruppierte sich C. triasii paraphyletisch zur Außengruppe Hispidella hispanica und machte die Crepis-Sektion Barkhausia in ihrer derzeitigen Abgrenzung polyphyletisch.
Keywords: Crepis; phylogeny; ddc:570